Entrepreneurship Orientation and Performance of Green Economy SMEs during COVID-19 Pandemic: The Mediating of Strategic Agility - Rofiaty Rofiaty; Ding Chong; Anis Nusron; Nindya Adha Yulianti; Sunaryo Sunaryo (Universitas Hayam Wuruk Perbanas, 2022)
This study was conducted to analyze the effect of entrepreneurial orientation on company performance through strategic agility. This research uses the SEM analysis method with WarpPLS software. The sample of this study consisted of 204 actors and strategic decision-makers of green economy SMEs in Malang areas. The unit of analysis in this study is the green economy SME business players in the business of flower, fruit, and ornamental plants. This business field was chosen because it is environmentally friendly, the waste has minimal risk of environmental damage, and this business is at the same time healthy for the environment for business people, employees, and consumers. Data collection was collected by distributing questionnaires directly or via a Google Form. This study proves that entrepreneurial orientation has a direct and positive effect on improving company performance. This study has proven that entrepreneurial orientation positively affects company performance both directly and through strategic agility, so it can be concluded that strategic agility can partially mediate the effect of entrepreneurial orientation on company performance. The application of strategic agility/agility is proven to improve company performance. This study can enrich the study of strategic management theory in the context of Strategic Agility in a green economy. SMEs’ owners and managers improve their performance by increasing entrepreneurial orientation and strengthening strategic agility.